Lormetazepam addiction: data analysis from an Italian medical unit for addiction - Faccini M; Leone R; Pajusco B; Quaglio GL; Casari R; Albiero A; Donati M; Lugoboni F (Dove Medical Press, 2012)
Marco Faccini,1 Roberto Leone,2 Benedetta Pajusco,1 Gianluca Quaglio,1 Rebecca Casari,1 Anna Albiero,1 Monia Donati,2 Fabio Lugoboni11Department of Internal Medicine, Addiction Unit, 2Pharmacology Unit, Reference Center for Education and Communication within the World Health Organization Program for International Drug Monitoring, University Hospital of Verona, Verona, ItalyBackground: The purpose of this study was to determine, in the context of a hospital addiction unit, which benzodiazepines were abused and to look for correlations with the characteristics of detoxified patients.Methods: A retrospective study was carried out using the database of hospital admissions to the addiction unit for detoxification from 2003 to 2010.Results: Of 879 admissions to the addiction unit during the seven-year period, 281 were for benzodiazepines. The percentage of patients addicted only to benzodiazepines was higher among females than males. Benzodiazepine consumption had started as a drug addiction behavior in only 10% of cases. The main sources of prescription identified were general practitioners (52% of cases) or compliant pharmacists (25%). Overall, 15 different benzodiazepines were abused, with lormetazepam being the most commonly used (by 123 patients, 43.8% of the total).Conclusion: Our data show that, outside the population of multidrug addicts, there is an underestimated group of chronic benzodiazepine consumers who are often not referred to medical institutions for treatment. Even in the group of patients addicted to one substance only, we observed an abnormal number of requests for detoxification from lormetazepam, which appears to be more "popular" than other benzodiazepines. This drug should be prescribed according to stricter criteria and submitted to closer control.Keywords: lormetazepam, benzodiazepines, addiction, inpatient detoxification